COMPREHENSIVE COGITATION ON FALLOUTS OF ESSENTIAL-TREMOR IN DENTISTRY IN ASSOCIATION WITH THE FIDELITY OF LABOUR AMONG DENTAL SURGEONS ACROSS TAMILNADU: A CROSS-SECTIONAL STUDY - Amrish D1, Rajmohan M2, Sindhu R3, Dinesh Dhamodhar2, Sathiyapriya S3, Prabu D4, Bharathwaj V V3, Vishali M5 (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Essential Tremor is the most common neurological disorder. However, dentists may have a higher risk of exposure to essential tremors in long way practice, and it also interferes with their perfection and accuracy of work. AIM: This study aims to find out the prevalence of essential tremors and their effect on the perfection of work among dental professionals in Tamilnadu. MATERIALS AND METHOD: A cross-sectional study was done using a self-validated questionnaire which consists of 16 close-ended and open-ended questions. This study was conducted among 100 practising dental professionals aged 25 to 50 in Tamilnadu, India, using a double-stage random sampling method. Statistical analysis was done using descriptive statistics and the Chi-square test, where p-value less than 0.05 was considered significant. RESULTS: The prevalence of essential tremors among dentists was 23%, and it had a positive association with biological age ( P value of 0.002) and years of clinical experience ( P value of 0.02). Also noted that rhythmic shaking of hands had a strong association with iatrogenic disease, mainly accidental pulp opening ( P value of <0.001) and other discomforts to the patient as well ( P value of < 0.001). CONCLUSION: Dentistry is a healing profession, and dentists are also more prone to various occupational hazards. Keeping in mind that "do no harm" is no longer possible with hand tremors. So, etiological factors associated with tremors should be ruled out, and with proper management, the person can be medically fit and start practising, which is entirely based on the dentist and their patients' confidence and comfort level. Keywords: essential tremors, dentists, the perfection of work, lifestyle changes, occupational hazards.